PENERAPAN MANAJEMEN MUTU TERPADU DALAM PENGUATAN KINERJA, KEPEMIMPINAN, DAN BUDAYA MUTU MADRASAH ALIYAH SWASTA - Paizaluddin, Paizaluddin; Herawati, Emy; Irama, Dedi; Abidin, Zainal; Pebrikarlepi, Erik (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study analyzes the application of integrated quality management in strengthening performance, leadership, and quality culture in Madrasah Aliyah (MA) Al-Ittifaqiah Indralaya. This study offers novelty by revealing how the principles of integrated quality management are adapted in the context of pesantren-based private madrasas, a domain that is still rarely explored in the Islamic education management literature. The research uses a qualitative descriptive method through in-depth interviews, observations, and documentation analysis involving madrasah heads, teachers, and education staff. The results of the study show that the implementation of integrated quality management has taken place through strategic planning, human resource development, and improvement of educational services. However, a number of obstacles are still faced, such as limited data-based supervision, long-term funding management, and uneven internalization of quality culture. These findings affirm the importance of visionary leadership, the participation of all madrasah residents, and government policy support to ensure the sustainability of quality improvement. This research contributes to the enrichment of TQM theory by presenting an application model that is in harmony with Islamic values and can be replicated in private madrassas in Indonesia and other Muslim countries.